High Expression of Ecto-Nucleotidases CD39 and CD73 in Human Endometrial Tumors. (24th February 2014) - Aliagas, Elisabet; Vidal, August; Texidó, Laura; Ponce, Jordi; Condom, Enric; Martín-Satué, Mireia
Abstract : One of the strategies used by tumors to evade immunosurveillance is the accumulation of extracellular adenosine, which has immunosupressive and tumor promoting effects. The study of the mechanisms leading to adenosine formation at the tumor interstitium are therefore of great interest in oncology. The dominant pathway generating extracellular adenosine in tumors is the dephosphorylation of ATP by ecto-nucleotidases. Two of these enzymes acting sequentially, CD39 and CD73, efficiently hydrolyze extracellular ATP to adenosine. They have been found to play a crucial role in a variety of tumors, but there were no data concerning endometrial cancer, the most frequent of the invasive tumors of the female genital tract. The aim of the present work is to study the expression of CD39 and CD73 in human endometrial cancer. We have analyzed protein and gene expression, as well as enzyme activity, in type I endometrioid adenocarcinomas and type II serous adenocarcinomas and their nonpathological endometrial counterparts. High levels of both enzymes were found in tumor samples, with significantly increased expression of CD39 in type II serous tumors, which also coincided with the higher tumor grade. Our results reinforce the involvement of the adenosinergic system in cancer, emphasizing the relevance of ecto-nucleotidases as emerging therapeutic targets in oncology.